Creep and microstructural development in P91 weldments at elevated temperature - Agyakwa, Pearl (2004)
This research concerns weldments in P91 steel and their creep behaviour. Its scope covers three main topics: the microstructure and creep response of the (i) weld metal, (ii) parent metal, and (iii) the effect of extended thermal exposure and creep on the weldments.